PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA FAKULTAS EKONOMI UNIVERSITAS SURAKARTA - Trisnowati, Juni (Universitas Slamet Riyadi, 2014)
This research aimed to analyze the influence of tangibles, reliability responsiveness, assurance, and empathy to the student satisfaction in Faculty of Economics Universitas Surakarta. The hypothesis in this study are: Suspected tangibles, reliability, responsiveness, assurance, and empathy have a significant effect to student satisfaction in Faculty of Economics Universitas Surakarta. Among the five variables, which variables have the most impact. The data required in this study is primary data and the sample was taken of 128 respondents using proportional random sampling techniques. Data collection methods used in this study is the questionnaire and performed analyzes with SPSS version 16,0, with the results all questionnaire are valid and reliable. Analysis of the data used in this study is a multiple linear regression and t test. The results of the data analysis in this study it can be concluded that the tangibles, reliability, responsiveness, assurance, and empathy have a significant effect to student satisfaction in Faculty of Economics Universitas Surakarta. Among the five variables, variable tangible that have the most impact. Keywords: tangibles, reliability, responsiveness, assurance, empathy and student satisfaction.